THE INFLUENCE OF WORK CLIMATE, ACHIEVEMENT MOTIVATION, AND DIGITAL LITERACY ON THE PERFORMANCE OF HIGH SCHOOL TEACHERS IN PRINGSEWU REGENCY - Istaridah, Devi (Institut Bakti Nusantara, 2024)
This study aims to analyze the influence of work climate, achievement motivation, and digital literacy on teacher performance in senior high schools in Pringsewu Regency. Using regression analysis methods, the study involved 98 teachers as respondents. The results show that the work climate significantly and positively impacts teacher performance, contributing 80.3%, with the regression equation Ŷ = 1.540 + 0.812X1. This indicates that a conducive work environment promotes improved teacher performance. Additionally, achievement motivation positively influences teacher performance by 69.30%, with the regression equation Ŷ = 6.406 + 0.877X2. High achievement motivation encourages teachers to work more optimally, boosting enthusiasm and energy in fulfilling teaching duties. Digital literacy, measured through work discipline, significantly and positively impacts teacher performance, contributing 87.6%, with the regression equation Ŷ = 1.802 + 0.965X3. Teachers' ability to leverage digital technology in teaching has been proven to enhance the quality of teaching and overall teacher performance. Simultaneously, work climate, achievement motivation, and digital literacy positively influence teacher performance, contributing 90.6%. The regression equation for the simultaneous effect is Ŷ = 1.071 + 0.355X1 + 0.064X2 + 0.688X3. These findings strengthen the argument that improving teacher performance requires creating a conducive work environment, providing appropriate motivation, and developing digital literacy. Therefore, the enhancement of educational quality is strongly influenced by these three factors, which collectively encourage teachers to achieve better performance and deliver higher-quality teaching.